Investigate and analysis the efficiency of photovoltaic system with active cooling based on numerical method - Nabeel Mohamed akram Samad; Khaleel Ali Khudhur; Ghanim Thiab Hasan (Institute of Advanced Engineering and Science, 2021)
The aim of this research is to establish a simulation model to examine the performance and working efficiency of a solar cell system by using computational fluid dynamics (CFD). The proposed model consists of a water feed tube and an absorber plate, as well as a convection heat transfer system, the ansys fluent system simulation program was used. The electrical output of the panel and its efficiency have been investigated and the effect of changes in the intensity of solar radiation on the temperature of the liquid and the absorption plate on the performance of the system have been studied. A dynamic analysis of the thermal hybrid system was performed with a circulation pump. Calculations were performed using a detailed mathematical model. The analysis was performed in three cases, the first case when the system has no cooling, in the second case with constant flow, and in the third case when the pump was optimized. Finally, numerical results were compared with the practical reference results. Both results are in good agreement. The results obtained showed that the system with optimization case give a good improvement in efficiency with low reduction of the thermal efficiency compared to a constant flow.